2016
DOI: 10.1177/0706743715620402
|View full text |Cite
|
Sign up to set email alerts
|

Precocious Initiation into Smoking, Alcohol Use, and Gambling among Children with Conduct Problems

Abstract: Objective: Adolescent participation in risky and addictive behaviours, such as smoking, substance use, and gambling has the potential to lead to many serious problems. The presence of conduct problems (CPs) and early initiation into risky and addictive behaviours have been independently shown to be associated with adolescent and young adult smoking, drinking, and gambling. Nevertheless, the relation between early initiation into risky and addictive behaviours and CPs remains to be explored among pre-adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This was after adjusting for demographic factors, household income, parental alcohol use, and self-perceived physical and mental health. Other observational studies have also found age at first alcohol use to be associated with social, behavioral, and mental health outcomes ( Agrawal et al, 2009 ; Blomeyer et al, 2011 ; Darke & Torok, 2014 ; Doran & Waldron, 2017 ; Hingson et al, 2016 ; Liang & Chikritzhs, 2012 ; Temcheff et al, 2016 ). However, few studies have investigated the extent to which early initiation of alcohol might be associated with violent behaviors such as weapon carrying among adolescents.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This was after adjusting for demographic factors, household income, parental alcohol use, and self-perceived physical and mental health. Other observational studies have also found age at first alcohol use to be associated with social, behavioral, and mental health outcomes ( Agrawal et al, 2009 ; Blomeyer et al, 2011 ; Darke & Torok, 2014 ; Doran & Waldron, 2017 ; Hingson et al, 2016 ; Liang & Chikritzhs, 2012 ; Temcheff et al, 2016 ). However, few studies have investigated the extent to which early initiation of alcohol might be associated with violent behaviors such as weapon carrying among adolescents.…”
Section: Introductionmentioning
confidence: 93%
“…Although various studies have investigated and found age at first alcohol use to be associated with adverse social, behavioral, and mental health outcome ( Agrawal et al, 2009 ; Blomeyer et al, 2011 ; Ciairano et al, 2009 ; Darke & Torok, 2014 ; Doran & Waldron, 2017 ; DuRant et al, 1999 ; Hingson et al, 2016 ; Liang and Chikritzhs, 2012 , 2015 ; Temcheff et al, 2016 ), to our knowledge, few studies have investigated the association between age at first alcohol use and weapon carrying among adolescents. Most of the existing studies tend to focus on the association between current alcohol use and weapon carrying among adolescents ( Bailey et al, 1997 ; DuRant et al, 1997 ; Goebert et al, 2004 ; Khubchandani and Price, 2018a , 2018b ; Muula et al, 2008 ), without taking into account the age at which adolescents had their first alcoholic drink.…”
Section: Introductionmentioning
confidence: 99%
“…However, the more crucial issue is tobacco use by adolescents, which has become a major concern in public health (5). Studies in this respect have suggested that symptoms of nicotine dependence are evident in the early stages of the onset of smoking because first, even by smoking a few cigarettes, adolescents intake the same amount of nicotine as that taken in by adults; and second, symptoms of smoking dependence including cravings and withdrawals occur in them (6,7). In this regard, investigations have also indicated that such symptoms develop quickly in adolescents and they will encounter numerous problems when trying to quit smoking (8).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood initiation of substance use is consequential. It is associated with future hazardous drinking (Liang & Chikritzhs, ), polysubstance use and comorbid mental disorders (SAMHSA, ), co‐occurring psychiatric illness including mood dysregulation disorder, and especially disruptive disorders including ADHD, Oppositional Defiant Disorder and Conduct Disorder (Deas & Thomas, n.d.; Temcheff, Déry, St‐Pierre, Laventure, & Lemelin, ), childhood assaultive behavior (Mathias et al., ), chaotic and abusive family environments and parental substance use disorders (Dube et al., ; Kingston, Rose, Cohen‐Serrins, & Knight, ), and adolescent suicide attempts (Cho, Hallfors, & Iritani, ). Because of the relationship of childhood substance initiation and co‐occurring and future morbidity and mortality, screening for childhood substance use would identify children who are likely to have multiple service needs including social services, mental health treatment, and treatment directed at specifically at substance use.…”
mentioning
confidence: 99%